Authoritative Agency for Tourism Zone: An Innovative Instrument for Destination Development? - Abdurahman, Benjamin (Research and Development Agency Ministry of Home Affairs, 2017)
Authority confusion in a development area in the region, especially on tourism destinations, has increased the government’s attention. The weaknesses of communication, coordination, and cooperation (3K) across sectors are suspected to be the source of the inhibiting problem. The actors who have various authorities run less synergistically and sometimes tend to prioritize their sector ego. The Ministry of Tourism currently prioritizes the concept of single destination - single management that is believed to answer the problem of development of tourism destinations in Indonesia. Ten tourism destinations have been established into national priority destinations as well as being the focus and locus of implementing this concept. To that end, the government through the Ministry of Tourism encourages the birth of institutions that have an integrity of authority, namely in the form of Tourism Authority Agency (BOP). But there are still other patterns that can be held, such as Destination Management Organization (DMO) in the context of Destination Governance (DG). The discussion of the concept of BOP as an instrument of tourism destination development in the region became the focus of writing this article. A discussion on BOP concept management pattern with DMO also needs to be done to be the source of consideration for policy improvement and planning for central and regional in the future.